Bulky hinge bracelet: inspired by batik sarung / Muhammad Saiful Hazim Mohamad Affandi - Mohamad Affandi, Muhammad Saiful Hazim (2022)
Batik is an inherent part of Malaysian identity. Batik motifs in Malaysia are mostly influenced by the Flora and Fauna. It's Quality and subtlety is the reason why Batik was added to UNESCO's Intangible Cultural Heritage of Humanity list in 2009.